xy -x - y =2
x.( y-1) = 2+ y
\(x=\frac{2+y}{y-1}=\frac{y-1+3}{y-1}=\frac{y-1}{y-1}+\frac{3}{y-1}=1+\frac{3}{y-1}\)
Để x nguyên
\(\Rightarrow\frac{3}{y-1}\in z\Rightarrow3⋮y-1\Rightarrow y-1\inƯ_{\left(3\right)}=\left(3;-3;1;-1\right)\)
nếu y- 1 = 3 => y =4 (TM) => x = 1+ 3/4-1 = 1 + 1 =2 => x= 2 (TM)
y-1 =-3 => y =-2 (TM) => x = 1+ 3/-2-1 = 1+(-1) =0 => x =0 (TM)
y -1 = 1 => y=2 (TM) => x = 1+ 3/2-1 = 1+3 =4 => x =4 (TM)
y-1 =-1 => y=0 (TM) => x = 1+ 3/0-1 = 1+(-3) = -2 => x = -1 (TM)
KL: (x;y) =........................................
Chúc bn học tốt !!!!!